The Function of Final w in Nouns and Adjectives in the Autography of Selected Late Egyptian Texts - Kilani, Marwan (Zeitschrift für ägyptische Sprache und Altertumskunde, 2017)
Late Egyptian texts are often characterized by the presence of a w at the end of words that does not seem to have any etymological justification. This w has often been interpreted as a “space filler”, i.e. a sign without any real function used by the scribe to fill spaces in the text. In the present article I question this hypothesis, and I suggest instead that these w were used to supply some information about the vocalization of the word, as sort of very primitive matres lectionis . Starting from the analysis of nouns and adjectives from a corpus of selected Late Egyptian texts, my study shows that there is a correlation between the presence or absence of the w in late Egyptian words and the vocalization in the corresponding Coptic reflexes. Possible further research and some considerations about the larger implications of this system are presented in the conclusions.